Event based transient notification architecture and NoSQL solution for astronomical data management : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Computer Science at Massey University, Albany (Auckland), New Zealand - Zhao, Yu (Massey University, 2015)
This thesis describes the development of a messaging system for astrophysical transient event notifications, and explores the use of NoSQL databases for astronomical data management. The Microlensing Observations in Astrophysics (MOA) Project is used as a case study for which respective implementations are provided. The Java Message Service (JMS) was chosen as the most suitable message implementation. Full implementation details of this new generation transient event notification architecture are described. It was found that the JMS-based architecture can provide a high performance on data delivery and could be up-scaled to meet high event rate situations. For NoSQL databasing, it was found that using a document-oriented database for astronomical data management is much easier than traditional relational databases, and significantly improves overall data access performance. In addition, a NoSQL database can be very easy to scale up in order to meet demands of large workload, and the scaling approach is very cost effective. Full design details of using a document-oriented NoSQL database for astronomical data management are presented in this thesis. The approaches developed in this research will provide scalable and efficient solutions for resolving similar computational challenges in astronomy. There are great opportunities to further extend this research and to make additional contributions to the field.
Keywords: Astronomy; Data processing; Non-relational databases